2022
DOI: 10.54751/revistafoco.v15n6-022
|View full text |Cite
|
Sign up to set email alerts
|

Práticas Ambientais Sustentáveis Como Fator De Escolha Dos Meios De Hospedagem

Abstract: O estudo busca responder a seguinte questão de pesquisa: as práticas sustentáveis desenvolvidas pelos meios de hospedagem é um fator decisivo de escolha pelos hóspedes? Assim, o objetivo do estudo foi identificar quais são os critérios de escolha que o hóspede está levando em consideração para escolher o meio de hospedagem. Neste horizonte, realizou-se uma pesquisa exploratória descritiva, que teve como instrumento de coleta de dados um questionário. O questionário foi aplicado aos hóspedes que estavam hospeda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…It was observed that the structures of the surveyed lodging facilities make use of natural elements in their designs. These include the utilization of natural lighting in the rooms (Figure 2 From the perspective of the lodging sector's significance, [14] asserted its relevance to the global economy as it contributes to economic and social development. However, in carrying out their activities, processes, and services, establishments within this sector generate environmental impacts that can contribute to global warming and the depletion of natural resources.…”
Section: General Aspects Of Lodging Facilities In Mossoró -Rnmentioning
confidence: 99%
See 2 more Smart Citations
“…It was observed that the structures of the surveyed lodging facilities make use of natural elements in their designs. These include the utilization of natural lighting in the rooms (Figure 2 From the perspective of the lodging sector's significance, [14] asserted its relevance to the global economy as it contributes to economic and social development. However, in carrying out their activities, processes, and services, establishments within this sector generate environmental impacts that can contribute to global warming and the depletion of natural resources.…”
Section: General Aspects Of Lodging Facilities In Mossoró -Rnmentioning
confidence: 99%
“…[5] identified that awareness of the significance of environmental management remains minimally disseminated within the organizational culture of lodging companies in Natal, Rio Grande do Norte. This situation is further underscored by [14], who examined if the sustainable practices implemented in lodging establishments were deciding factors in choosing these enterprises (with 65.46% indicating 'no' or 'never considered'). Thus, [5] stated that environmental management still contributes in a limited manner to the competitiveness of lodging establishments.…”
Section: Smart Switchesmentioning
confidence: 99%
See 1 more Smart Citation